Konsep Ekonomi Islam; Pemikiran Abu Yusuf - Nahlah, Nahlah; Kara, Muslimin; Ambo Masse, Rahman; Hamka, Hamka (Prodi Ekonomi Syariah Universitas Majalengka, 2024)
Abu Yusuf was a Fuqaha (Fiqih Expert) during the Abbasid Daula. Abu Yusuf served as chairman of the supreme court. Abu Yusuf has a famous work on taxation, namely the book Al-Kharaj. This book was written at the request of Caliph Harun Ar Rashid. This paper aims to find out Abu Yusuf's thoughts on economics in the book of al-Kharaj. The method used in this writing is the method of library research or literature study. As well as the data sources used are secondary data in the form of journals, theses, and articles related to the theme of writing. The study results found that the Al-kharaj Book not only discusses taxation but also discusses sources of state income, namely ghanima, fa'i, kharaj, 'ushr, jizya and zakat. In the book of al-Kharaj, Abu Yusuf recommends the use of the Muqasama system (proportional tax) rather than the Misahah system (fixed tax), which was in effect from the time of Caliph Umar to the early period of the Abbasid dynasty with a value that did not burden farmers. In addition, Abu Yusuf was also the first to formulate that price is not only determined by the power of supply but also by the power of demand. Several other factors are also thought to influence prices, such as the money supply in the country, hoarding, and monopoly.